Clinical view of gynecologic intraoperative frozen section diagnosis - Alexander B. Olawaiye; Chengquan Zhao (BMJ Publishing Group, 2022)
Intraoperative consultation includes gross evaluation and frozen section, which is an integral component of surgical oncology for many reasons. First, it allows appropriate surgical procedures to be undertaken. Second, it can potentially protect the patient from a second procedure. Third, it helps towards counselling of patients and their family members and lastly, it facilitates early management planning. Utilization of frozen section is justified by the reported sensitivity, specificity, positive and negative predictive values all of which are as high as 90-100% in some studies. It is very important for gynecologists to have good communication with pathologists, especially for cases with an indeterminate, frozen result. Discussion with the pathologist can help the gynecologist understand the diagnostic dilemma and the differential diagnosis, which can help them make best surgical decisions.